2020
DOI: 10.1007/978-3-030-35582-1_8
|View full text |Cite
|
Sign up to set email alerts
|

CD200-CD200R Pathway in the Regulation of Tumor Immune Microenvironment and Immunotherapy

Abstract: Tumor-associated inflammation and immune responses are key components in the tumor microenvironment (TME) that regulate tumor growth, progression and metastasis. Tumorassociated myeloid cells (TAMCs) are a group of cells that play multiple key roles including induction of tumor-associated inflammation/angiogenesis and regulation of tumor-specific T cell responses. Thus, identification and characterization of key pathways that can regulate TAMCs are of critical importance for developing cancer immunotherapy. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…6a ). DC_C3_LAMP3 cells were also predicted to interact with CD8_C11_PDCD1 cells through CD200-CD200R signalling, a non-classical immune-suppressive pathway involved in the suppression of anti-tumour responses 37 (Fig. 6b ).…”
Section: Resultsmentioning
confidence: 99%
“…6a ). DC_C3_LAMP3 cells were also predicted to interact with CD8_C11_PDCD1 cells through CD200-CD200R signalling, a non-classical immune-suppressive pathway involved in the suppression of anti-tumour responses 37 (Fig. 6b ).…”
Section: Resultsmentioning
confidence: 99%
“…CD200 receptor (CD200R) is an immunoregulatory receptor prominently expressed in the lungs, and mainly reported among alveolar macrophages, neutrophils, mast cells 9 11 . Previous studies have shown CD200-deficient mice have increased pulmonary alveolar macrophage activity in a mouse influenza model, which leads to increased mortality and hindered resolution of pulmonary inflammation 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It interacts with the transmembrane glycoprotein CD200, which can be expressed on a variety of cells, including CD4 + and CD8 + T cells and tumor cells. CD200/CD200R signaling has been linked to the regulation of macrophage activation and appears to inhibit T cell responses [ 42 ]. CD200R1 was highly upregulated on TAMs compared to macrophages from normal lung (LFC = 4.0, p < 0.0001) and, to a lesser degree, on CD8 + T cells (LFC = 1.65, p .adj = 0.01).…”
Section: Resultsmentioning
confidence: 99%